BAGAIMANA PRAKTIK MANAJEMEN LABA DAN PENGHINDARAN PAJAK SEBELUM DAN SETELAH PANDEMI COVID19 DI INDONESIA? - Amrie Firmansyah; Risanto Ardiansyah (Center for Economic Studies Universitas Katolik Parahyangan, 2020)
This study investigates the difference between tax avoidance and earnings management, consisting of accrual earnings management and real earnings management. Also, this study investigates the association between accrual earnings management and real earnings management with tax avoidance in the pandemic era. The research data is sourced from financial reports of consumers goods industry companies listed on the Indonesia Stock Exchange from 2019 to 2020, obtained from www.idx.co.id. Based on purposive sampling, the total sample in this study amounted to 74 observations. Hypothesis testing in this study employed paired sample t-test or Wilcoxon Non-Parametric Test to examine the comparative hypothesis and multiple regression analysis for cross-section data to examine the correlative hypothesis. This study suggests no difference in tax avoidance, accrual earnings management, real earnings management level in the pandemic era compared to the pra-pandemic era. This study also concludes that real earnings management is negatively associated with tax avoidance during the pandemic, while accrual earnings management is not associated with tax aggressiveness. The Indonesia Tax Authorities need to improve monitoring and control procedures related to tax avoidance activities conducted by companies.